The World Cancer Research Fund/American Institute for Cancer Research Third Expert Report on Diet, Nutrition, Physical Activity, and Cancer: Impact and Future Directions - Clinton, Steven K; Giovannucci, Edward L; Hursting, Stephen D (The Journal of nutrition, 2020)
The Third Expert Report on Diet, Nutrition, Physical Activity, and Cancer: A Global Perspective by the World Cancer Research Fund (WCRF) and the American Institute for Cancer Research (AICR) represents the most comprehensive, detailed, and objective analysis of the accumulated research in the discipline. The report provides a framework for public health efforts around the globe by governments and other organizations with the goal of significantly reducing the burden of cancer, enhancing health, and improving quality of life for cancer survivors. Coupled with the WCRF/AICR Continuous Update Panel reports on specific cancers, these efforts also provide guidance to healthcare practitioners engaged in counseling individuals who may benefit from diet and lifestyle changes. Most critically, this report defines priorities for future research efforts that will improve the evidence base of future recommendations both for population-based public health efforts and increasingly for more personalized strategies targeting individuals who are cancer survivors or at risk due to genetic predisposition or carcinogenic exposures.